Increased sLRP1 and decreased atrial natriuretic peptide plasma levels in newly diagnosed T2DM patients are normalized after optimization of glycemic control - García, Eduardo; Gil, Pedro; Miñambres, Inka; Benitez-Amaro, Aleyda; Rodríguez, Claudia; Claudi, Lene; Julve, Josep; Benitez, Sonia; Sánchez-Quesada, Jose Luís; Rives, Jose; Garcia-Moll, Xavier; Vilades, David; et al. (Frontiers in Endocrinology, 2023)
Low-density lipoprotein receptor-related protein (LRP1) negatively modulates circulating atrial natriuretic peptide (ANP) levels. Both molecules are involved in the regulation of cardiometabolism.To evaluate soluble LRP1 (sLRP1) and ANP levels in people with newly diagnosed type 2 diabetes mellitus (T2DM) and determine the effects of metabolic optimization.This single-center longitudinal observational study recruited patients with newly diagnosed T2DM (n = 29, HbA1c > 8.5%), and 12 healthy control, age-and sex-matched volunteers. sLRP1 and ANP levels were measured by immunoassays at T2DM onset and at one year after optimization of glycemic control (HbA1c ≤ 6.5%).T2DM had higher sLRP1 levels than the control group (p = 0.014) and lower ANP levels (p = 0.002). At 12 months, 23 T2DM patients reached the target of HbA1c ≤ 6.5%. These patients significantly reduced sLRP1 and increased ANP levels. Patients who did not achieve HbA1c < 6.5% failed to normalize sLRP1 and ANP levels. There was an inverse correlation in the changes in sLRP1 and ANP (p = 0.031). The extent of sLRP1 changes over 12 months of metabolic control positively correlated with those of total cholesterol, LDL cholesterol, TG, TG/HDLc, and apolipoprotein B.Newly diagnosed T2DM patients have an increased sLRP1/ANP ratio, and increased sLRP1 and decreased ANP levels are normalized in the T2DM patients that reached an strict glycemic and metabolic control. sLRP1/ANP ratio could be a reliable marker of cardiometabolic function.